A study of corrosive-chemical properties and biocompatibility of submicrocrystalline titanium of BT1-0 grade - Filipenko, Volodymyr; Sevidova, Katerina; Dedukh, Ninel; Malyshkina, Svitlana; Simonova, Anastasiya; Timchenko, Iryna; Moskalenko, Vladyslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
A comparative assessment of ВТ1-0 samples with different crystalline structures according to criteria of their corrosive-electrochemical activity and results of medical-biological studies is given. It is shown that nano- and submicrocrystalline titanium preserves high biocompatibility indices, which are typical for macrocrystalline analogues.